Faktor-Faktor Yang Mempengaruhi Tingkat Kemiskinan Di Provinsi Jawa Timur Tahun 2014-2022 - Khoirudin, Rifki; Haerusman, Agung (Journal of Regional Economics and Development, 2023)
Poverty is one of the problems in the complex and fundamental Indonesian economy. Need to find a solution to overcome or at least reduce the level of poverty. This study was conducted to determine the influence of gross regional domestic product variables, unemployment, education, the minimum wage of the province and the human development index as a free variable against the level of poverty in East Java as a bound variable. The analysis used is quantitative analysis with the Fixed Effect Model (FEM) method in Panel Data with time series data from 2014 to 2022 and cross section 38 district/city data in East Java and the conclusion is that all free variables used in this study have significant effect on the number of poor population in East Java, both simultaneous and partial.